BOARD SIZE AND BOARD GENDER DIVERSITY ON BANKING PERFORMANCE IN INDONESIA - Saeh, Charlen; Tulung, Joy E.; Saerang, Regina T. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
The banking industry in Indonesia plays a fundamental role in driving national economic growth and improving people's welfare. This research aims to fill the gap by examining the effect of board size and the relationship between gender diversity on the board on banking performance in Indonesia in the last 5 years. This research is using a quantitative method with the entire conventional banks in Indonesia as the population. Sampling technique that used purposive sampling technique, the total sample 52 banks. Data processing using STATA 17 software with multiple linear regression as the analysis method. The result shows that partially Board Size have a positive effect on banking performance, while Board Gender Diversity as measured using the Blau Index, have a negative effect on banking performance partially. But simultaneously, both the independent variables, Board Size and Board Gender Diversity, have a significant effect on banking performance. Hopefully, conventional banks in Indonesia pay more attention on maintaining the composition of the board and improving gender equality by creating a work environment that values diversity, providing equal opportunities for everyone, and eliminating gender bias in recruitment and promotion processes.    Keyword: Board Size, Board Gender Diversity, Banking Performance